The processing of biometric data under the European data strategy, between risks of mass surveillance and protection of fundamental rights (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
The contribution reconstructs the theme of mass surveillance, intertwined with the protection of personal data. It starts to investigate the criticality profiles connected to the treatment of some specific categories of data, in particular biometric data, the treatment of which –systematically and on a large scale – is likely to define new surveillance models.Under these profiles, the article analyzes the jurisprudence of the European Court of Human Rights and Court of Justice.
Keywords: surveillance; biometric data; data protection